Short-animation video in web meeting classes for secondary school learners' EFL writing achievement - Sari, Dwi Nikita; Susilo, Susilo; Limbong, Efendi (ELT Forum: Journal of English Language Teaching, 2021)
The study aims at investigating whether there is an effect of short animation video on the EFL narrative writing achievement of the secondary school EFL learners in the circumstance where web meeting was becoming the class. The study was an experimental study using Static Group Comparison Design. Respondents participated in the study were the 8th Graders of SMP Negeri 18 Samarinda, Indonesia. There were 32 students in the experimental group and the other 32 students in the control group. The data were collected by conducting writing tests, i.e. post-test for both the experimental and control groups. Independent sample t-test was used to test the significant difference for pre and post-test scores. The results revealed that the students under the experimental group (M = 83.22, SD = 7.979, N = 32) performed higher in scores on their narrative writing achievement than the students under the control group (M = 76.00, SD = 9.824, N = 32), t(32) = 3.227, p < .002, two-tailed. It means there is a significant difference between narrative writing achievement of the students under the experimental group and those under the control group. This finding implies there is a significant effect of short animation video on the narrative EFL writing achievement of the secondary school EFL learners.